Spatial distribution of enhanced BrO and its relation to meteorological parameters in Arctic and Antarctic sea ice regions - S. Seo; A. Richter; A.-M. Blechschmidt; I. Bougoudis; J. P. Burrows (Atmospheric Chemistry and Physics, 2020)
Satellite observations have shown large areas of elevated bromine monoxide (BrO) covering several thousand square kilometres over the Arctic and Antarctic sea ice regions in polar spring. These enhancements of total BrO columns result from increases in stratospheric or tropospheric bromine amounts or both, and their occurrence may be related to local meteorological conditions. In this study, the spatial distribution of the occurrence of total BrO column enhancements and the associated changes in meteorological parameters are investigated in both the Arctic and Antarctic regions using 10 years of Global Ozone Monitoring Experiment-2 (GOME-2) measurements and meteorological model data. Statistical analysis of the data presents clear differences in the meteorological conditions between the 10-year mean and episodes of enhanced total BrO columns in both polar sea ice regions. These differences show pronounced spatial patterns. In general, atmospheric low pressure, cold surface air temperature, high surface-level wind speed, and low tropopause heights were found during periods of enhanced total BrO columns. In addition, spatial patterns of prevailing wind directions related to the BrO enhancements are identified in both the Arctic and Antarctic sea ice regions. The relevance of the different meteorological parameters on the total BrO column is evaluated based on a Spearman rank correlation analysis, finding that tropopause height and surface air temperature have the largest correlations with the total BrO vertical column density. Our results demonstrate that specific meteorological parameters can have a major impact on the BrO enhancement in some areas, but in general, multiple meteorological parameters interact with each other in their influence on BrO columns.